Body iron excretion - Green, Ralph (My University, 1975)
An attempt was made to document iron losses from the body as a whole, as well as from individual excretory routes using a combination of radioisotopic and chemical techniques. The purpose of this work was to gain a better understanding of external body exchange, and to resolve some of the existing controversies regarding the magnitude of daily iron losses. The basis for this controversy is extensively reviewed in the thesis
A thesis submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, for the degree of Doctor of Medicine.
Keywords: Human Body; Iron; Pathology; Skin; Gastrointestinal Hormones